Taxonomic and nomenclatural novelties in some Cactaceae of Greater Antilles - Guiggi, Alessandro; Mariotti, Mauro (Phytotaxa, 2022)
The recently debated identity and incertus status of Cereus serruliflorus, Opuntia taylorii, O. tuna. and of its presumed close relatives, O. dillenii and O. jamaicensis from the Caribbean region, are here investigated to clarify the correct application of the names through an analysis of the protologues, original material, and examination of other specimens. One new endemic species to Jamaica (O. kingstoniana) was described; O. repens subsp. taylorii comb. nov. is proposed; an epitipe was designated for Cactus tuna (≡ O. tuna) and Cereus serruliflorus (≡ Serrulatocereus serrulatus); O. jamaicensis is here accepted as a valid species, distinct from O. tuna sensu auct.